BIMG-05. TO BE OR NOT TO BE GLYCOLYTIC: DEUTERATED GLUCOSE-BASED ASSESSMENT OF THE WARBURG EFFECT ALLOWS NON-INVASIVE IMAGING OF TUMOR BURDEN AND TREATMENT RESPONSE IN MUTANT IDH GLIOMAS IN VIVO. (25th March 2021) - Taglang, Celine; Batsios, Georgios; Tran, Meryssa; Gillepsie, Anne Marie; Luchman, Hema Artee; Pieper, Russell O; Ronen, Sabrina M; Viswanath, Pavithra
Abstract: The Warburg effect, characterized by elevated glucose uptake and flux to lactate, is a metabolic hallmark of cancer. Recent studies have identified deuterium 2 H-magnetic resonance spectroscopy (MRS) using 6, 6'- 2 H-glucose as a novel method of imaging the Warburg effect in high-grade primary glioblastomas (GBMs). However, its utility for imaging low-grade gliomas has not been tested. The goal of this study was to determine whether 6, 6'- 2 H-glucose can be used for imaging tumor burden and treatment response in mutant isocitrate dehydrogenase (IDHmut) low-grade gliomas in vivo . We examined mice bearing orthotopic tumors of the patient-derived BT257 astrocytoma model. 1 H-MRS, providing a readout of steady-state metabolite levels, confirmed the presence of 2-hydroxyglutarate, the product of IDHmut, in BT257 tumor tissue but not normal brain. Previous studies comparing IDHmut gliomas with GBMs suggest that IDHmut gliomas undergo lactate dehydrogenase silencing, potentially leading to a non-glycolytic phenotype. Nevertheless, our results indicated that, compared to normal brain, glucose uptake and concomitant flux to lactate were significantly higher in BT257 tumor tissue. Importantly, 6, 6'- 2 H-glucose metabolism to lactate was observed in BT257 tumor-bearing mice, but not tumor-free mice. Furthermore, imaging studies confirmed spatial localization of lactate production to the tumor vs. contralateral normal brain. We then examined the ability of 6, 6'- 2 H-glucose to assess treatment response. Poly-(adenosine 5′-diphosphate-ribose) polymerase inhibitors (PARPi) inhibit IDHmut glioma growth and are in clinical trials for IDHmut glioma patients. Treatment with the PARPi niraparib reduced 6, 6'- 2 H-glucose flux to lactate in BT257 tumor-bearing mice. Importantly, this reduction was observed at early time-points when no difference in tumor volume could be detected using anatomical imaging, pointing to the ability of 6, 6'- 2 H-glucose to assess pseudoprogression. Collectively, our results suggest that IDHmut gliomas display a glycolytic phenotype amenable to non-invasive 2 H-MRS-based imaging of tumor burden and treatment response.